ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BELI KONSUMEN DODOL PULUT RIA DI KECAMATAN TANJUNG PURA - Adek Puja Wiyanda; Thursina Mahyuddin; Hanisah, Hanisah (Bajang Institute, 2025)
This research was conducted at Ria's dodol pulut business in Tanjung Pura District. This aim was carried out to analyze the influence of product quality, price, distribution and promotion on consumer buying interest in dodol pulut Ria in Tanjung Pura District. The research method used in this research is the survey method. This research uses a causal research design. The sampling technique uses accidental sampling. The number of research respondents was 40 consumers interested in Dodol Pulut Ria. The data used in this research are primary data and secondary data. The data analysis technique used is Multiple Linear Regression. Data processing was carried out using the SPSS Program Version 23. The results of this research show that product quality, distribution and promotion have a significant effect on consumer buying interest in dodol pulut Ria in Tanjung Pura District and the price variable does not have a significant influence on consumer buying interest in dodol pulut Ria in Tanjung District Temple.